Validation of the proposed model of effective classroom management for teenagers with learning disabilities and late learners - Mahmoudi, Mehdi; Ranjdoust, Shahram; Azimi, Mohamad (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2022)
Background and Aim: research indicates that learning disorders are highly prevalent and on the other hand, using a defective classroom management approach in the classroom of all age groups has a serious coexistence with other disorders. The aim of this study was to validate the optimal model of an effective classroom management program for teenagers with learning disabilities and late learners. Method: This research had two methods; First, using a survey method to validate the classroom management model, and then using a pseudo-experimental method and a pre-test-post-test design with a control group, the effectiveness of the classroom management model was determined. The statistical population included teachers and teenage students of one district of Urmia city. The analysis method of the first stage was one-sample t-test and the second stage was covariance, which was used with SPSS software. Results: The findings of the first stage showed that the proposed model of classroom management for adolescents with learning disabilities and late learners is valid from the point of view of experts, and the findings of the second stage also showed that the use of the proposed model significantly improves academic performance; test group increased (p≥0.005). Conclusion: Considering the validity of the proposed model from the point of view of experts and also the effectiveness of using this model in classroom management, it is suggested that the proposed model be used in the classroom management of students with learning disabilities.